2007
DOI: 10.1073/pnas.0610906104
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inhibition of cardiac ERK1/2 promotes stress-induced apoptosis and heart failure but has no effect on hypertrophy in vivo

Abstract: MAPK signaling pathways function as critical regulators of cellular differentiation, proliferation, stress responsiveness, and apoptosis. One branch of the MAPK signaling pathway that culminates in ERK1/2 activation is hypothesized to regulate the growth and adaptation of the heart to both physiologic and pathologic stimuli, given its known activation in response to virtually every stress-and agonist-induced hypertrophic stimulus examined to date. Here we investigated the requirement of ERK1/2 signaling in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
204
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(222 citation statements)
references
References 36 publications
12
204
1
5
Order By: Relevance
“…56 Genetic inhibition of cardiac ERK1/2 promotes stress-induced apoptosis and heart failure. 57 Thus, the reduction of ERK1/2 activity could be part of the mechanisms by which cardiac Gab1 deficiency led to an increase in apoptosis and loss of hypertrophic growth in Gab1-cKO mice under TAC. On the other hand, p38 MAPK acts as an enhancer of myocyte apoptosis and cardiac pathologies and is believed to play a causative role in DCM in the cardiac stress responses.…”
Section: Resultsmentioning
confidence: 99%
“…56 Genetic inhibition of cardiac ERK1/2 promotes stress-induced apoptosis and heart failure. 57 Thus, the reduction of ERK1/2 activity could be part of the mechanisms by which cardiac Gab1 deficiency led to an increase in apoptosis and loss of hypertrophic growth in Gab1-cKO mice under TAC. On the other hand, p38 MAPK acts as an enhancer of myocyte apoptosis and cardiac pathologies and is believed to play a causative role in DCM in the cardiac stress responses.…”
Section: Resultsmentioning
confidence: 99%
“…There is a large body of evidence showing an activation of extracellular signal-related kinase-1/2 in response to many known hypertropic agonists. 48,49 However, Purcell et al 50 have recently shown that extracellular signal-related kinase-1/2 signaling is not required for mediating physiological or pathological cardiac hypertrophy in vivo; moreover, blockade or deletion of cardiac Figure 5 Cluster analysis of genes selectively normalized by QHI in late LVH. The transcripts differentially expressed in late LVH were then filtered to select out those selectively normalized by the QHI treatment group and average linkage hierarchical cluster analysis of this cohort was then performed to graphically illustrate their expression profile.…”
Section: Signal Transductionmentioning
confidence: 99%
“…A central signaling cascade, which has been shown to promote the development of cardiac hypertrophy, is the mitogen-activated protein (MAP) kinase cascade consisting of the kinases rapid activation of fibrosarcoma (Raf), MAP/ERK kinase (MEK1/2), and ERK1/2. However, inhibition of ERK1/2-mediated hypertrophy using dominant-negative mutants or MEK inhibitors in isolated cardiomyocytes and in mice was accompanied by increased cardiomyocyte death (6)(7)(8)(9)(10)(11)(12)(13). Therefore, to date, it has not been possible to exploit the potential of the ERK1/2 cascade as a therapeutic target in cardiac hypertrophy.…”
mentioning
confidence: 99%